The perfect vagina : cosmetic surgery in the twenty-first century - McDougall, Lindy (Indiana University Press, 2021)
The Perfect Vagina highlights the complexities involved with Female Genital Cosmetic Surgery, its role in Western beauty culture, and the creation and control of body image in countries where self-care is valorized and medicine is increasingly harnessed for enhancement as well as health.